Compound Words In Dawan Language - I Wayan Budiarta (RETORIKA: Jurnal Ilmu Bahasa, 2016)
The purpose of this study is to find out the structure of compound words and the types of compound words in Dawan language. This study belongs to qualitative research as it aimed to describe qualitatively the structure and the types of compound words in Dawan language. The data are taken from language consultants (informants) of Dawan language speaker. In collecting the data, the researcher prepares questionnaire and applied interview method. The result of analysis showed that compound words in Dawan language are structured by combining two different words whether the words in the same category or different category. The structure of compound words are built by combining  noun (N) with noun (N), for instance mais-oni ‘sugar’ which is built by the noun mais ‘salt’ and the noun oni ‘sweet’; noun (N) with verb (V), for instnace  bife-anaot ‘prostitute’ which is built by the noun bife ‘woman’ and the verb anaot ‘work’; verb (V) with noun (N), for instance poni-haano  ‘propose’ which is built by  the verb poni ‘hang’ and the noun hauno ‘leaf’;  verb (V) with verb (V), for instance fua-tulu  ‘worship’ which is built by  the verb fua ‘see’ and the verb tulu ‘give’; and noun (N) with adjective (Adj), for instance ume-kbubu ‘kitchen’ which is built by the noun ume ‘house’ and the adjective kbubu ‘circle’. Further analysis on the compound words showed that they can also be classified into noun head word, verb head word, and adjective head word. Keywords: compound words, noun head word, verb head word, adjective head word.